2020
DOI: 10.2147/ott.s222821
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-766 Promotes The Proliferation, Migration And Invasion, And Inhibits The Apoptosis Of Cutaneous Squamous Cell Carcinoma Cells By Targeting PDCD5</p>

Abstract: This study aimed to investigate the regulatory role and mechanism of microRNA-766 (miR-766) on cutaneous squamous cell carcinoma (CSCC) cells. Methods: The expression of miR-766 and programmed cell death 5 (PDCD5) was detected in CSCC tissues and CSCC cell lines (A431, SCL-1 and DJM-1 cells) by qRT-RCR. The proliferation, colony-forming ability, apoptosis, migration and invasion of A431 and SCL-1 cells was measured by MTT, colony formation, flow cytometry, wound healing and transwell assay, respectively. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…MMP-2 and MMP-9 genes play a significant part in squamous cell carcinoma metastasis (26). For example, microRNA (miR)-766 promotes the invasion and migration of squamous cell carcinoma cells A431 and SCL-1 by releasing MMP-2 and -9 (27). In CSCC cells, overexpression of LINC00520 significantly inhibits migratory and adhesive capacity by downregulating MMP-2 mRNA and MMP-9 protein levels (28).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 and MMP-9 genes play a significant part in squamous cell carcinoma metastasis (26). For example, microRNA (miR)-766 promotes the invasion and migration of squamous cell carcinoma cells A431 and SCL-1 by releasing MMP-2 and -9 (27). In CSCC cells, overexpression of LINC00520 significantly inhibits migratory and adhesive capacity by downregulating MMP-2 mRNA and MMP-9 protein levels (28).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-766 sped up A431 and SCL-1 cells’ motility, invasion, and proliferation, while also boosting MMP-2 and MMP-9. As a result, miR-766 can increase proliferation migration and invasion, of CSCC cells by reducing the level of PDCD5 expression ( 104 ). Additionally, through increasing HOXA9, miR766-3p downregulation inhibited CSCC cell growth, metastasis, and glycolysis ( 174 ).…”
Section: Mir-766mentioning
confidence: 99%
“…On the CSCC, the precise regulatory impact of miR-766 is still unknown. Recently, Liu et al (104), suggested that miR-766 might function in CSCC cells as an oncomiRNA. They discovered that in CSCC cells and tissues, miR-766 expression was elevated whereas PDCD5 expression was downregulated.…”
Section: Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%
“…MiR-142-5p targets PTEN ( Bai et al, 2018 ), miR-186 targets reticulophagy regulator 1 ( Xinde Hu et al, 2019 ), and miR-320a regulates autophagy related 2B ( Bi et al, 2021 ) to inhibit cancer cell apoptosis. Programmed cell death 5 is the dominant downstream target of miR-766, the upregulation of which inhibits the apoptosis of CSCC cells ( Liu et al, 2020 ). Increased expression of miR-22 decreases CSCC chemosensitivity by targeting the Wnt/β-catenin signaling axis, thus promoting malignant progression ( Yuan et al, 2021 ).…”
Section: Noncoding Rnas In Skin Cancermentioning
confidence: 99%
“…MiR-142-5p targets PTEN (Bai et al, 2018), miR-186 targets reticulophagy regulator 1 (Xinde , and miR-320a regulates autophagy related 2B (Bi et al, 2021) to inhibit cancer cell apoptosis. Programmed cell death 5 is the dominant downstream target of miR-766, the upregulation of which inhibits the apoptosis of CSCC cells (Liu et al, 2020).…”
Section: Figurementioning
confidence: 99%